Pedoman Pemberian Tablet Tambah Darah (TTD) Bagi Remaja Putri Di Madrasah Aliah Negeri 2 Makassar - Hafsah Hafsah; Husnul Hatima; Nurul Fitrahminarsih N; Nirwana Nirwana; Nurayni Wahdaniyah; Ainun Azzarah Annur; Hutri Rara Panggalo (Jurnal Pengabdian Bidang Kesehatan, 2023)
Anemia is one of the health problems, especially adolescent girls in developing countries. The World Health Organization (2021) shows that the prevalence of anemia in women of reproductive age (15-49) in the world in 2019 is around 29.9%. Balitbangkes 2018 states that in Indonesia anemia in adolescent girls ranges from 27.2% in the age group 15-24 years. The cause of anemia is generally due to lack of knowledge about anemia, lack of iron, folic acid, vit B12 and vit A. One of the government's efforts in preventing anemia is the consumption of blood supplement tablets. However, there are still many adolescent girls who are not compliant with consuming them, which have been distributed free of charge, this is due to the lack of awareness and knowledge of adolescent girls about the benefits of taking blood supplement tablets. So it is necessary to provide alternative solutions that are able to increase awareness and knowledge for adolescent girls about the benefits of consuming blood tablets. This activity is part of the Tridharma Community Service of Almarisah Madani University. This activity was carried out in November 2023. The method used in this service is counseling. The purpose of this service is to increase knowledge and compliance for adolescent girls at MAN 2 Makassar to routinely consume Blood Addition Tablets to prevent the incidence of anemia. Thus, it is hoped that the program run by the government can run accordingly